Dancing with the missional theology and praxis: the shifts from Lausanne Covenant 1974 to Cape Town Commitment 2010 - Loh, Pak (Hill Road, 2012)
Lausanne 1974 provided a catalytic momentum that shaped the evangelical mission landscape, particularly in its missional theology and strategy. Firstly, from a theological perspective, there is no doubt that the greatest contribution of this conference to the world evangelical Christians is the Lausanne Covenant. The fifteen paragraphs of the Covenant was so well crafted that they managed to strike a balance between the aspirations of radical and conservative evangelicals. Secondly, in terms of the strategy, the conference gave a clear picture of the need to focus on the unreached people groups. Ralph Winter's impassioned presentation challenged the delegates to look beyond their geopolitical boundaries to the needs of the "ethne" (nations), which he defined as peoples with their own unique social ethno-linguistic culture and identity. This new definition of "ethne" marked a watershed moment for global mission. It triggered such a forceful missional alarm that it became the dominant theme of evangelical mission. It was also the impetus for a new missional drive called, "Frontier Mission Movement." This movement, which occupied much of the attention and resources of evangelical missions in the 1980s and 1990s, promoted a mindset to finish the task of world evangelization by the year 2000. The broader frontier mission movement was immersed in the tasks defined by the newly coined term, "10/40 Window." Unfortunately, the evangelistic zeal was so intense that it wiped out many other theological perspectives and missional voices of the Lausanne Conference. In particular, the conviction of the integral mission which the Lausanne Covenant clearly promoted － "evangelism and socio-political involvement are both part of Christian duty" － was totally ignored. It is true that great progress has been made in regard to reaching unreached peoples. Nevertheless, this dominance of the theology of closure and missional praxis to finish world evangelization by the year 2000 has brought forth deep frustration in many Latin American Christian leaders, for example, René Padilla and Samuel Escobar. The seven missional shifts highlighted in this paper provide brief vignettes of the missiological developments from 1974 to 2010, revealing the consequences of this zealous push for frontier missions.
Keywords: Evangelicalism – Missions; Frontiers (Mission agency); International Congress on World Evangelization (1st : 1974 : Lausanne; Switzerland); International Congress on World Evangelization (3rd : 2010 : Cape Town; South Africa); Missions – Strategy; Theology; Evangelical